Parameters involved in the internal reverse logistics of a hospital pharmacy - Yui, Kao Pei; Candida Compagnoni dos Reis, Camila; Moro, Matheus Fernando; Flores, Sandrine de Almeida; Morales Garza, Adriana Yolanda; Cortes Berghauser, Neron Alípio; Weise, Andreas Dittmar (Brazilian Journal of Operations & Production Management, 2017)
This research aims to identify the causes linked to internal reverse logistics of materials and medicines in a hospital, covering studies for process optimization performed by this department. The study is based on a hospital located in the State of Paraná, Brazil. First, observations were performed through visits during the months of September/2015 to April/2016, and the month of March was chosen for the collection of data. Also, "in loco" visits were carried out for better understanding the process that occurs in both of the drug shipment to patients, as the internal reverse logistics was performed with drugs. To collect the data a survey form was used on the main reasons for discarding of drugs and materials for the central pharmacy. The instrument was adapted from the form used by the institution aimed specifically to the Intensive Care Unit. Through the observations made in the Hospital Unit, it was revealed that the company has a structured logistics process, standardized, and has a fundamental tool for this: information technology, creating efficient, reliable and fast data, requiring however, some improvements aiming primarily to prevent and reduce waste of both time and materials/medicines.